Aerophilic Triphase Interface Tuned by Carbon Dots Driving Durable and Flexible Rechargeable Zn-Air Batteries - Ding, Kuixing; Ye, Yu; Hu, Jiugang; Zhao, Liming; Jin, Wei; Luo, Jia; Cai, Shan; Weng, Baicheng; Zou, Guoqiang; Hou, Hongshuai; Ji, Xiaobo (Nano-Micro Letters, 2023)
Efficient bifunctional catalysts for oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) are vital for rechargeable Zn-air batteries (ZABs). Herein, an oxygen-respirable sponge-like Co@C–O–Cs catalyst with oxygen-rich active sites was designed and constructed for both ORR and OER by a facile carbon dot-assisted strategy. The aerophilic triphase interface of Co@C–O–Cs cathode efficiently boosts oxygen diffusion and transfer. The theoretical calculations and experimental studies revealed that the Co–C–COC active sites can redistribute the local charge density and lower the reaction energy barrier. The Co@C–O–Cs catalyst displays superior bifunctional catalytic activities with a half-wave potential of 0.82 V for ORR and an ultralow overpotential of 294 mV at 10 mA cm−2 for OER. Moreover, it can drive the liquid ZABs with high peak power density (106.4 mW cm−2), specific capacity (720.7 mAh g−1), outstanding long-term cycle stability (over 750 cycles at 10 mA cm−2), and exhibits excellent feasibility in flexible all-solid-state ZABs. These findings provide new insights into the rational design of efficient bifunctional oxygen catalysts in rechargeable metal-air batteries. Highlights: 1 Oxygen-respirable sponge was constructed by carbon dots-assisted synthesis strategy. 2 The hydrophilicity and aerophilicity of Co@C–O–Cs active sites boost oxygen diffusion and the bifunctional oxygen reduction reaction and oxygen evolution reaction activities. 3 Co@C–O–Cs-based Zn-air battery (ZAB) displays excellent specific capacity and stability, and the all-solid-state Co@C–O–Cs-based ZAB exhibits excellent flexibility.